Dimensi Metrik Dominasi Pada Graf Globe dan Graf Pendant Globe - Muchammad Abrori; Atifah Rahmah; Deddy Rahmadi (Limits: Journal of Mathematics and Its Applications, 2026)
The dominating metric dimension of a graph is defined as the minimum cardinality of a set that is both a resolving set and a dominating set. A node is said to be an is a differentiating set if for every two different vertices  holds  and said to be a set of a dominant if there is at least one node adjacent to the set domination. The Globe  graph is a graph obtained from two protected vertices connected by  paths of length two. The Pendant Globe Graph is  is a graph obtained from a globe graph by adding paths along it . This research discusses the metric dimensions and dominant metric dimension on the globe graph  for  as well as metric dimensions on the pendant globe graph for  and . The method in this research begins with the concept of metric dimension, the concept of metric dimension then dominant continued with the introduction of the characteristics of globe graphs and pendant globe graphs. Furthermore, the metric dimension and dominance dimension will be sought in globe graphs and pendant globe graphs for  vertices.